Structures in gas–liquid churn flow in a large diameter vertical pipe - Sharaf, Safa; van der Meulen, G. Peter; Agunlejika, Ezekiel O.; Azzopardi, Barry J. (Elsevier, 2016)
Gas–Liquid two phase co-current flow in a vertical riser with an internal diameter of 127 mm was investigated in the churn flow pattern. This paper presents detailed experimental data obtained using a Wire Mesh Sensor. It shows that the most obvious features of the flow are huge waves travelling on the liquid film. Wisps, large tendrils of liquid and the product of incomplete atomisation, which had previously detected in smaller diameter pipes, have also been found in the larger diameter pipe employed here. The output of the Wire Mesh Sensor has been used to determine the overall void fraction. When examined within a drift flux framework, it shows a distribution coefficient of ∼1, in contrast to data for lower gas flow rates. Film thickness time series extracted from the Wire Mesh Sensor output have been examined and the trends of mean film thickness, that of the base film and the wave peaks are presented and discussed. The occurrence of wisps and their frequencies have been quantified.